Productivity and nutrient composition of cucumber (Cucumis sativus L.) grown under integrated application of vermicompost, phosphorous and zinc fertilizers - Turna, Tamanna Tahmid; Syed, Mahmud; Rahman, Md Khalilur (Dhaka University Journal of Biological Sciences, 2023)
To evaluate the integrated effect of vermicompost, phosphorous, and zinc fertilizer on plant yield and nutritional quality of cucumber (Cucumis sativus L.), a pot experiment was conducted in the net house at Soil, Water, and Environment Department of the University of Dhaka. In this study, eight treatments viz. T1: control, T2: VC6 t ha-1, T3: P25 kg ha-1, T4: Zn1.5 kg ha-1, T5: VC6 t ha-1 + P25 kg ha-1, T6: VC6 t ha-1 + Zn1.5 kg ha-1, T7: P25 kg ha-1 + Zn1.5 kg ha-1, T8: VC6 t ha-1 + P25 kg ha-1 + Zn1.5 kg ha-1 with three replicates were used by following a completely randomized design (CRD). A one-way ANOVA with a Tukey posthoc test revealed statistically significant differences in growth and yield metrics between the treatments (p ≤ 0.05). The maximum growth and yield contributing attributes viz. plant height (123 cm), leaf number (30 plant-1), leaf area (155.45 cm2), stem girth (2.70 cm), branch number (18 plant-1), fruit number (7 plant-1), and fruit fresh (382 g) and dry (33 g) weight were detected in the treatment VC6 t ha-1 + P25 kg ha-1 + Zn1.5 kg ha-1 (T8). The treatment T1 (control) exhibited the lowest values for all the aforementioned treatments. The nutrient quality attributes in fruits were analyzed highest in the same treatment T8. So, farmers are advised to apply VC6 t ha-1 + P25 kg ha-1 + Zn1.5 kg ha-1 in their fields because it can help make land management and cucumber production more sustainable. Dhaka Univ. J. Biol. Sci. 32(2): 201-210, 2023 (July)